Is 'deep-water formation' in the Baltic Sea a key to understanding seabed dynamics and ventilation changes over the past 7, 000 years?. (10th June 2020) - Moros, Matthias; Kotilainen, Aarno Tapio; Snowball, Ian; Neumann, Thomas; Perner, Kerstin; Meier, H.E. Markus; Leipe, Thomas; Zillén, Lovisa; Sinninghe Damsté, Jaap S.; Schneider, Ralph
Abstract: Numerous hydro-acoustic studies of the seabed of the Baltic Sea have revealed the unusual occurrence of sediment contourite drifts and re-suspension at greater water depths. In addition, radiocarbon dating of bulk sediments indicates significant age reversals. We present new geophysical, sediment proxy data (including extensive radiocarbon dating) and hydrographic measurements, which are combined with results of numerous marine geological studies performed during the last decades. These data indicate that a deep-water formation process significantly affected the seabed dynamics during regional climatically cold phases during the last c. 7, 000 years. We propose that, during the colder periods (e.g. the Little Ice Age), newly formed bottom waters likely caused widespread re-suspension of organic carbon-rich laminated sediments that were deposited during the preceding warm periods in shallower areas, and this material was transported to and re-deposited in the deeper parts of the Baltic Sea sub-basins. In our scenario, a topographic feature, known as the Baltic Sea Klint, acted as a hydrographic barrier for deep-water formed in the northern Baltic. Thus, during the cold periods increased lateral matter influx from the northern Baltic led to the accumulation of much thicker macroscopically homogenous clayey sediments in sub-basins north of the Klint. Moreover, deep-water formation produced bottom currents that led to the formation of sediment contourite drifts at water depths of >200 m in the Bothnian Sea, the Åland Deep and northern central Baltic Sea sub-basins. Bottom water ventilation in the Baltic Sea is generally assumed to be determined solely by the inflow of oxygen-rich, saline water from the North Sea, but we challenge this assumption and postulate that deep-water formation is a key process that ventilates the bottom waters of the Baltic Sea during climatically cold periods with substantial implications for its sedimentary archive.